Practice, enactivism, and ecological psychology. (April 2023) - McKinney, Jonathan; Steffensen, Sune Vork; Chemero, Anthony
The Course-of-Experience Framework (CEF) represents a promising path forward for embodied and enactive approaches to cognitive science. It aims to provide a comprehensive explanation of representation-hungry activities by grounding cognition in practice. Practice is not merely something that we do as a means to an end, but is constitutive of cognition. Puzzlingly, however, the CEF begins to develop a distributed approach to cognition by viewing individuals through their cultural-cognitive ecology or milieu, before shifting focus to an internalist interpretation of enactive agency. CEF states that the agent enacts their world and discovers themselves through practice, but provides no clear account of organism-environment mutuality. This is problematic because CEF's notion of practice depends on organism-environment mutuality in its first core assumption. The tendency to downplay the importance of the environment is likely due to a holdover of early enactivist ideas that have sparked tensions between ecological psychology and enactivism in the past. We attempt to re-align the CEF with the enactive project, which we think is gradually shifting away from individualistic concepts like autopoiesis and sense-making toward social and ecological concepts like participatory sense-making and affordances.